Developmental Trajectories of Maladaptive Perfectionism among African American Adolescents - Herman, Keith C. (2013)
The present study examined the developmental trajectories of maladaptive perfectionism over a seven-year period among African American youth living in an urban setting (N=547). In particular, the study attempted to determine whether two maladaptive aspects of perfectionism (socially-prescribed and self-critical) changed over time and could be distinguished by variables in 6(th) and 12(th) grade (mean age at study entry (first grade) was 6.22 years (SD = 0.34)). Four classes best described the developmental trajectories on both measures of maladaptive perfectionism: high; low; increasing; and decreasing. Sixth and twelfth grade correlates, including measures of internalizing symptoms mostly confirmed the distinctiveness of these classes. Parallel process analyses suggested that the two processes are complementary, yet distinct. Implications regarding the prevention of maladaptive perfectionism are discussed.